Assessing creative problem-solving competencies in primary school educators: A confirmatory factor analysis approach - Charoentham, Mai; Kantathanawat, Thiyaporn; Pimdee, Paitoon; Teerasoonthontai, Krittameth (Edelweiss Applied Science and Technology, 2025)
This study aimed to examine and analyze the second-order confirmatory factor structure of creative problem-solving for primary school teachers. The sample consisted of 150 teachers and educational supervisors from the Office of the Basic Education Commission, selected through multi-stage random sampling. The data collection tool was a creative problem-solving questionnaire evaluated for item-objective congruence (IOC) values between 0.60 and 1.00, with discriminant power ranging from 0.68 to 0.88 and reliability coefficients between 0.77 and 0.92. Data were analyzed using means, standard deviations, and second-order confirmatory factor analysis (CFA). The results revealed that teachers and educational supervisors had a high level of agreement on creative problem-solving in general and for each component. The second-order CFA creative problem-solving model demonstrated a good fit with the empirical data and consisted of five components and 15 indicators. The components, ranked by weight from highest to lowest, were Truth Discovery (TD), reflecting the emphasis teachers place on understanding the nature and context of problems. This was followed by Knowledge Creation (KC), which highlights the importance of applying knowledge to real-world challenges, and Problem Identification (PI). Idea Generation (IG) and Solution Discovery (SD) received slightly lower scores, though still within the high range. This suggests that while teachers value these components, they may require further development in fostering innovation and evaluating solutions critically.